Strategic Marketing and Supply Resilience in Small-Scale Coffee Roasteries: An Integrated SWOT–QSPM Approach to Sustaining Competitive Performance - Barly, Kanya Fadilla; Eka Ardhi, Fredy (Journal of Supply Chain and Entrepreneurship, 2026)
Background: The rapid growth of the coffee industry in Indonesia has intensified competition among small-scale coffee roasteries, requiring firms to adopt adaptive and data-driven marketing strategies. Despite strong regional production potential, many coffee SMEs experience unstable sales performance due to limited market reach and vulnerability to supply fluctuations. These challenges indicate the need for an integrated strategic approach that aligns marketing decisions with supply resilience to sustain competitive performance. Aims: This study aims to identify internal and external strategic factors influencing roasted coffee marketing, formulate feasible strategic alternatives, and determine priority strategies that enhance both marketing effectiveness and supply resilience in a small-scale coffee roastery context. Methods: A quantitative descriptive approach was employed using primary data collected through interviews and structured questionnaires involving key managerial actors and expert judgment. Strategic analysis was conducted using the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS), followed by the Internal–External (IE) matrix to determine strategic positioning. Alternative strategies were generated through SWOT analysis and evaluated using the Quantitative Strategic Planning Matrix (QSPM) to identify priority actions. Results: The findings reveal that the firm is positioned in the “hold and maintain” quadrant, indicating moderate internal strength and external opportunity. Seven strategic alternatives were identified, with the highest priority strategy emphasizing the maintenance of raw material quality through strengthened supplier partnerships. This strategy is critical in addressing supply instability while reinforcing customer trust and product consistency. Conclusion: This study demonstrates that integrating marketing strategy with supply resilience is essential for sustaining competitive performance in small-scale coffee roasteries. Rather than relying solely on promotional expansion, strategic emphasis on supply stability and product quality creates a more robust competitive foundation. The proposed SWOT–QSPM integration offers a systematic and transferable decision-making framework for SMEs facing similar structural constraints. Strengthening upstream supply relationships not only mitigates operational risks but also enhances long-term market positioning, making resilience-oriented marketing a key driver of sustainable business performance in emerging coffee industries.